(The Effect of Dried Cassava Addition on The Copra Press to The Quality of Coconut Oil and Defatted Coconut Produced) - M. Maman Rohaman; Solechan -; Endang Tri W; Tatit K Bunasor (Warta Industri Hasil Pertanian, 1996)
A study was on the effect of dried cassava addition on the copra press to the quality of coconut oil and defatted coconut produced.In the study the treatment employed were dried cassava addition(0%,10%,20%,and 30%),size (slice and shreded) and cooking treatment (cooked and uncooked).The coconut oil was observed for yield,moisture content,free fatty acid (ffa),and clarity.Deffated coconut was observed for moisture,sh,fat,protein and cabohydrate content.Organoleptic/sensoric test was done on the product of deffated coconut (the cookies).The best result was obtained from those with 30% dried cassava addition,shredded coconut and cassava floor and cooked.The analitycal data of coconut oil are 62.52% yield,1.34% moisture content 0.28% ffa and  59.6% clarity.The analytical data of deffated coconut are 8.39% moisture content,4.07%ash,27.865 fat,12.32% protein and 47.98% carbohydrate.Panelists accepted its product by scoring 3.23-3.77(normal-like).